Adaptive Polar Sampling: A New MC Technique for the Analysis of Ill-behaved Surfaces - Luc Bauwens; Charles S. Bos; Herman K. van Dijk (Tinbergen Institute, 1998)
Adaptive Polar Sampling is proposed as an algorithm where random drawings aredirectly generated from the target function (posterior) in all-but-onedirections of the parameter space. The method is based on the mixed integrationtechnique of Van Dijk, Kloek & Boender (1985) but extends this one by replacingthe one-dimensional quadrature step by Monte Carlo simulation from thisone-dimensional distribution function.The method is particularly suited for the analysis of ill-behaved surfaces. Anillustrative example shows the feasibility of the algorithm.
Keywords: 330; Markov Chain Monte Carlo sampling; Ill-behaved surfaces; Polar coordinates; Stichprobenverfahren; Theorie